2015
DOI: 10.3389/fpls.2015.00417
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive survey of the grapevine VQ gene family and its transcriptional correlation with WRKY proteins

Abstract: WRKY proteins are a class of transcription factors (TFs) involved in the regulation of various physiological processes, including the plant response to biotic and abiotic stresses. Recent studies in Arabidopsis have revealed that some WRKY TFs interact with a class of proteins designed as VQ proteins because of their typical conserved motif (FxxxVQxLTG). So far, no information is available about the genomic organization and the function of VQ motif-containing protein in grapevine (Vitis vinifera L). In the cur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
92
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(100 citation statements)
references
References 76 publications
(130 reference statements)
5
92
0
3
Order By: Relevance
“…This result is consistent with previous studies that most GmVQ genes can repond to SA treatment in soybean [17,22]. Similar cases for VQ genes under SA treatment were also reported in other species, such as Arabidopsis [11], grapevine [13], and Chinese cabbage [14]. In Arabidopsis, the expression levels of many SA-induced VQ genes peaked at early hours (e.g., 4 h post treatment) and some of them started to decline as time progressed further (e.g., 12 h or particularly 24 h post treatment) [11].…”
Section: Expression Analysis Of Ntvq Genes In Response To Biotic and supporting
confidence: 93%
See 2 more Smart Citations
“…This result is consistent with previous studies that most GmVQ genes can repond to SA treatment in soybean [17,22]. Similar cases for VQ genes under SA treatment were also reported in other species, such as Arabidopsis [11], grapevine [13], and Chinese cabbage [14]. In Arabidopsis, the expression levels of many SA-induced VQ genes peaked at early hours (e.g., 4 h post treatment) and some of them started to decline as time progressed further (e.g., 12 h or particularly 24 h post treatment) [11].…”
Section: Expression Analysis Of Ntvq Genes In Response To Biotic and supporting
confidence: 93%
“…There are six variations of the conserved VQ motif among the 59 NtVQ proteins: FxxxVQxLTG (33/59), FxxxVQxFTG (10/59), FxxxVQxVTG (4/59), FxxxVQxYTG (3/59), FxxxVQxLTA (6/59), FxxxVQxLTV (2/59). In previous studies, it was known that there are six types of motifs in Arabidopsis (LTG, FTG, VTG, YTG, LTS, and LTD) [11], six types in maize (LTG, FTG, VTG, ITG, ATG, and LTA) [16], four types in rice (LTG, FTG, VTG, and ITG) [13], six types in Chinese cabbage (LTG, FTG, VTG, YTG, LTV, and LTS) [14], five types in Moso bamboo (LTG, FTG, VTG, ITG, and LTA) [18], five types in soybean (LTG, FTG, VTG, LTS, and LTR) [22], four types in apple(LTG, FTG, VTG, and LTC) [20], three types in grapevine (LTG, FTG, and VTG) [13] and seven in tomato (LTG, FTG, VTG, LTS, LTA, YTG, and HTG) [24]. Comparing the different variations of conserved VQ domain in the above plant species, we can see LTG, FTG, and VTG are the three most common ones for the VQ domain in plants.…”
Section: In-silico Analysis Of Ntvq Genesmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous reports showed that some rice and grape WRKY genes were co-expressed with VQ 373 genes during the response to attacks by three different pathogens [50,51] CmWRKY genes were co-expressed with 11 CmVQ transcription factors (Fig 6). Furthermore, 379 some of the co-expressed CmWRKY and CmVQ genes were shown to be response to powdery 380 mildew infection, implying that these VQ and WRKY proteins are involved in the same biological 381 pathway.…”
mentioning
confidence: 82%
“…The cis-regulatory elements were identified using PlantCARE (http://bioinformatics.psb.ugent.be/webtools/plantcare/html/) software (Wang et al, 2015). …”
Section: Methodsmentioning
confidence: 99%